Test of human acid, for the production of castilla frijol (Vigna unguiculata L.), in the experimental field of the anitos province of Barranca - Legua Cardenas, José Antonio (2019)
The research was conducted in the Los Anitos experimental field and aims todetermine the doses of humic acid, in castilla beans, started in November 2015, thetreatments were established (T1 = 00, T2 = 50, T3 = 100, T4 = 150 ml Liqhumus /20 l. Water), the application was made in three moments, it was evaluated until harvestand laboratory. This experiment was carried out in four treatments and four blocks,using the Design of Block Completely Random (DBCA). The statistical analysis thatwas performed was the analysis of variance at 1%, 5%, and Duncan’s test at 5%. Theresults were obtained in which the highest dose (150 ml / 20 l water) stood out theT4 with 48,075 cm of height, 28,55 number of flowers, 42,44 sampling of numberof pods per plant, 103,63 g. sampling of pod weight and 2,501 Tm / ha commercialyield, in laboratory good results were determined with: 18.35 cm of pod length, 12.67number of grains per pod, 0,43 g grain weight per pod and 23,62 g, however, all werein the medium range (18 - 25 g). Also stood out in higher profitability is 45,92%